Synthesis of air stable silver nanoparticles and their application as conductive ink on paper based flexible electronics. (July 2014) - Li, W.; Chen, M.; Li, W.; You, C.; Wei, J.; Zhi, L.
Abstract : Air stable silver nanoparticles (NPs) at a high concentration (up to 0·2M) were synthesised by the reduction in Ag + ions with glucose in cetyltrimethylammonium bromide (CTAB) solutions, for preparing nano-Ag ink applicable for direct writing on photo paper using a gel ink pen. The reaction was performed at room temperature, and the input of extra inert gas was not necessary. The UV/vis spectrum exhibited an absorption band at 413 nm, revealing the formation of Ag NPs. By the analysis of X-ray diffraction (XRD), the resultant particles were confirmed to be pure Ag with a face centred cubic structure. From the (high resolution) TEM analysis, it was found that the mean diameter of Ag NPs was 16·5 nm, and the morphology of the particles exhibited highly crystalline nature. In addition, the excess of CTAB was effective in reducing the aggregation and size of the Ag NPs and in improving their air stability. The reduced size and enhanced air stability of the Ag NPs resulted in an improved particle density upon sintering, which was mainly responsible for the increased conductivity of the Ag patterns. The resistivity of Ag patterns sintered at 160°C for 2 h was 6·8±0·8 μΩ cm, 4·2 times the bulk resistivity. A sample paper based electrode and circuits were successfully made, and all of them exhibited excellent flexibility and good conductivity, which can be used as part of some flexible electronic devices, such as triboelectronic generator, solar cells and radio frequency identification antenna, etc.